Telephina and Other Trilobites from the Pratt Ferry Beds, Ordovician of Alabama, U.S.A. (May 2014) - Shaw, Frederick C.
Abstract : The Pratt Ferry beds are a three meter thick bioclastic carbonate unit containing the Pygodus serrus – P. anserinus conodont zone boundary and lying just below the Nemagraptus gracilis graptolite zone at a single locality in Alabama. Telephina Marek at Pratt Ferry and other eastern North American localities is represented by at least six species. These are judged widespread and in part conspecific with Scandinavian or Asian forms of similar age. Most of the fifteen Appalachian telephinid species proposed by Ulrich (1930) are reviewed and some synonymized. Bevanopsis Cooper is present, extending its stratigraphic range via B. buttsi (Cooper). The original description of Ceraurinella buttsi Cooper is augmented. Other recorded but poorly represented genera include Ampyxina, Arthrorhachis, Calyptaulax, Hibbertia, Lonchodomas, Mesotaphraspis, Porterfieldia, and Sphaerexochus . The entire faunule represents a mixture of 'inshore' and 'offshore' or planktonic faunal elements rarely seen elsewhere in the latest Middle Ordovician (Darriwilian) of eastern North America.